Pengaruh Leverage, Profitabilitas, Dan Ukuran Perusahaan Terhadap Tax Avoidance Sektor Transpormasi - Fazria, Rizka; Lubis, Salsabila Azzahro; Fadilah, Alma Hafsa; Afriliyani, Intan; Azzahra, An Suci (CV. ITTC INDONESIA, 2025)
The purpose of this study is to evaluate the effect of leverage, profitability, and company size on tax prevention in the transformation and logistics industry during the period 2021-2024. Businesses use legal tax planning methods to avoid taxes by not violating tax laws. A quantitative method, comparative causal approach, was used in this study. The study population consisted of 37 businesses, which were taken as a sample of 18 businesses using purposive sampling technique. There were 72 observation data and 5 outlier data were excluded from the population, which resulted in a total of 67 observation data. While the independent variables consist of leverage (DAR), profitability (ROA), and total asset size of the company (Log Natural Assets), the dependent variable for tax avoidance is proxied by the Rate of Cash Effective Tax (CETR). The results show that only business size has a partially negative effect on tax avoidance; leverage (p=0.646) and profitability (p=0.686) have no effect. Three variables have a significant effect on tax prevention simultaneously (F=3.368; p=0.024), with the ability to explain 12.8% of the variation (R2 = 0.128).